Measuring the influence of the Camp de Tarragona high-speed rail station on first-time and repeat tourists visiting a coastal destination - Òscar Saladié; Salvador Anton Clavé; Aaron Gutiérrez (Belgeo, 2016)
This paper explores the effects of high-speed rail (HSR) services on the destination choice of first-time tourists and repeat tourists arriving in the Costa Daurada, a mature coastal destination in Catalonia, using HSR services. The analysis is based on a probabilistic method and uses data from a survey of HSR passengers at the Camp de Tarragona HSR station during the summer of 2014. It concludes that the increase in probability of visiting this particular destination because of the existence of the HSR station among this specific group of visitors is quite larger in the case of first-time tourists (23.9%) than in repeat tourists (12.9%). At the same time, significant differences are found in the profiles of both segments of HSR passengers.